Integrating Deep Learning and Data Analytics for Enhanced Business Process Mining in Complex Enterprise Systems (Journal of Artificial Intelligence & Research, 2021)
The integration of deep learning with data analytics offers significant advancements in the field of business process mining, particularly within complex, multi-departmental enterprise systems. This research explores the application of deep learning algorithms, such as convolutional neural networks (CNNs) and recurrent neural networks (RNNs), to enhance the accuracy and scalability of business process mining techniques. By leveraging large volumes of event logs, transactional data, and unstructured information, this study demonstrates how data analytics, coupled with deep learning, can uncover hidden patterns, optimize workflows, and provide actionable insights for process improvements. Furthermore, the paper highlights the challenges and opportunities inherent in the adoption of these technologies within large organizations, focusing on data quality, system integration, and computational complexity. Through the analysis of case studies from diverse sectors, including finance, manufacturing, and logistics, the research illustrates the practical implications of these innovations in real-world enterprise environments. The integration of deep learning and data analytics is poised to redefine the capabilities of business process mining, offering organizations the tools needed to achieve higher levels of operational efficiency, cost reduction, and decision-making precision.